Историк права Ф. В. Тарановский - Michalczenko, Sergiej (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2004)
The paper is devoted to the life and activities of an outstanding historian of law and state, F. W. Taranowski (1875–1936), a disciple of F. I. Leontiev. F. W. Taranowski graduated form the Warsaw University to become recognized as a researcher of Germanand French law of 18th century. He wrote numerous books on the theory and encyclopedia of law, including the famous handbook published in 1917 and reprinted in 1923. After the revolution of 1917 Taranowski emigrated to Yugoslavia. He lectured at the Belgrade University and he wrote several books and papers on the history of law of Southern Slavs.

Artykuł jest poświęcony życiu i działalnoœci wybitnego historyka prawa i państwa F. W. Taranowskiego (1875–1936), ucznia F. I. Leontiewa, F.W. Taranowski byłabsolwentem Uniwersytetu Warszawskiego, uznanie zdobył jako badacz prawa niemieckiego i francuskiego XVIII wieku. Napisał szereg książek z dziedziny teorii i encyklopedii prawa, w tym słynny podręcznik, wydany w roku 1917 i ponownie w roku 1923. Po rewolucji 1917 roku Taranowski znalazł się na emigracji w Jugosławii. Wykładał na uniwersytecie w Belgradzie i napisał kilka książek i artykułów o historii prawa południowych słowian.
F. W. Taranowski - Historian of Law